Simian Immunodeficiency Virus Infection Mediated Changes in Jejunum and Peripheral SARS-CoV-2 Receptor ACE2 and Associated Proteins or Genes in Rhesus Macaques - Boby, Nongthombam; Cao, Xuewei; Williams, Kelsey; Gadila, Shiva Kumar Goud; Shroyer, Monica N.; Didier, Peter J.; Srivastav, Sudesh K.; Das, Arpita; Baker, Kate; Sha, Qiuying; Pahar, Bapi (Frontiers in Immunology, 2022)
Angiotensin converting enzyme-2 (ACE2) and associated proteins play a pivotal role in various physiological and pathological events, such as immune activation, inflammation, gut barrier maintenance, intestinal stem cell proliferation, and apoptosis. Although many of these clinical events are quite significant in HIV/SIV infection, expression profiling of these proteins has not been well reported. Considering the different pathological consequences in the gut after HIV infection, we hypothesized that the expression of ACE2 and associated proteins of the Renin-angiotensin system (RAS) could be compromised after SIV/HIV infection. We quantified the gene expression of ACE2 as well as AGTR1/2, ADAM17, and TMPRSS2, and compared between SIV infected and uninfected rhesus macaques (Macaca mulatta; hereafter abbreviated RMs). The gene expression analysis revealed significant downregulation of ACE2 and upregulation of AGTR2 and inflammatory cytokine IL-6 in the gut of infected RMs. Protein expression profiling also revealed significant upregulation of AGTR2 after infection. The expression of ACE2 in protein level was also decreased, but not significantly, after infection. To understand the entirety of the process in newly regenerated epithelial cells, a global transcriptomic study of enteroids raised from intestinal stem cells was performed. Interestingly, most of the genes associated with the RAS, such as DPP4, MME, ANPEP, ACE2, ENPEP, were found to be downregulated in SIV infection. HNFA1 was found to be a key regulator of ACE2 and related protein expression. Jejunum CD4+ T cell depletion and increased IL-6 mRNA, MCP-1 and AGTR2 expression may signal inflammation, monocyte/macrophage accumulation and epithelial apoptosis in accelerating SIV pathogenesis. Overall, the findings in the study suggested a possible impact of SIV/HIV infection on expression of ACE2 and RAS-associated proteins resulting in the loss of gut homeostasis. In the context of the current COVID-19 pandemic, the outcome of SARS-CoV-2 and HIV co-infection remains uncertain and needs further investigation as the significance profile of ACE2, a viral entry receptor for SARS-CoV-2, and its expression in mRNA and protein varied in the current study. There is a concern of aggravated SARS-CoV-2 outcomes due to possible serious pathological events in the gut resulting from compromised expression of RAS- associated proteins in SIV/HIV infection.